The Best Laid Plans - Sidney Sheldon (UK HarperCollins Publishers, 1998)
In his rise to the presidency of the United States, lawyer Oliver Russell felt he had to jettison his love, Leslie Stewart. But Leslie also rose, becoming a newspaper tycoon in Washington and now she intends to even the score.
Keywords: Literature (3GdCOHs; General -- Fiction; Newspaper publishing; Presidents -- United States -- Fiction; A Novel